العقيدة تقرير و مصادر التلقي في أحمد بن اسماعيل الگورانى فی النظر واالستدالل منهج - كريم, أ.د. عبدالله محمد; محمد, نوزاد إبراهيم (Sulaimani Journal for Humanities, 2023)
Knowledge of consideration and reasoning and its study yields insight into deriving legal rulings and solves multiple problems. Inference is the request for evidence and its report to prove the meaning, and the evidence is not intended by itself, but rather it is a means to reach the intended. Adhering to the Book and the Sunnah, adjudicating them in issues of belief, venerating them and not rejecting anything from them is the first thing that characterizes the methodology of the predecessors of the nation in establishing the belief. The Almighty said: (But no, by your Lord, they will not believe, until they call you to arbitrate in their disputes, and then find within themselves no resentment regarding your decisions, and submit themselves completely) (Surah an Nisa' 65) Confining yourself to the Qur’an and the Sahih Sunnah, as they are the main source of the Islamic faith. Standing at the concepts of legal texts and understanding their implications and not delving into them with false interpretations. Obtaining the reward from God Almighty, with love, desire and impulse to serve the Islamic faith.